Exploring Student Motivation in Quranic Memorization in Selected Islamic Secondary Schools (a Case Study) - Nik Md Saiful Azizi Nik Abdullah; Fathiyah Solehah Mohd Sabbri; Rabi'atul Athirah Muhammad Isa (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2021)
This article sought to explore the student motivation in memorizing the Quran. A qualitative study through semi-structured interviews with six participants was done to gain data for this study. The findings showed that parents, teachers and the participants themselves influenced student motivation in memorising the Quran. The role of parental guidance and advice was the most influential factor leading to cause among students in learning the Quran. Implications of this study, the students themselves and teachers also were the source of motivation to memorize. At the same time, teachers should always assist and help students in their memorization of the Quran. That way, students will feel more confident to continue their memorization. Therefore, this study can be helpful as a reference in lowering the gap in motivation in Quranic memorization. Hence, the researchers believe that this study will help the other researchers continue and elaborate more on Quranic memorization about the cause.